REWORKING THE WORKPLACE connecting people, purpose and place - Gillen, Nicola; Pickering, Richard (London : RIBA PUBLISHING, 2023)
The office has changed forever. Emerging from the pandemic, the workplace has undergone its greatest disruption since the dawn of the service economy. Covid has rewritten the rule book about how, when, where and even why we work.
Cover -- Title -- Copyright -- Contents -- Acknowledgements -- Author Biographies -- Foreword -- Introduction -- Part I People -- 1. The Impact of the Covid-19 Pandemic on Work, Culture and Community -- 2. Hybrid Working -- 3. The Impact of Buildings on Well-Being -- 4. Delivering Positive Social Impact -- Part II Purpose -- 5. Operationalising the Workplace Experience -- 6. The Value and Purpose of Place -- 7. Experience Destinations -- Part III Place -- 8. Evolution of Cities -- 9. The Physical-Virtual Interface -- 10. Ecosystems, Communities and Placemaking -- Conclusion -- Notes
Keywords: Offices -- Designs and plans; Office buildings -- Social aspects; Architecture -- Human factors; ARCHITECTURE / Public, Commercial, or Industrial Buildings; ARCHITECTURE / General